Development of ovary in Assam goat from birth to six months of age-A histomorphometrical study* - KALITA, A; BAISHYA, G; BHATTACHARYA, M (The Indian Journal of Animal Sciences, 2013)
Ovaries from 21 femak Assam goats were studied months wise from bitth to 6 months of age. They were divided into 7 age-groups consisting of 3 animals in each group. The contex of ovary contained different types of follicles, viz. primordial, primary, early secondary, late secondary and Graafian follicles. The mean diameter of follicle, oocyte and nucleus of both right and left ovaries gradually increased with the advancement of age. Most of the values for the mean diameter of follicle, oocyte and its nucleus were nonsignificantly higher In the left ovary than those observed in the right. The diameter of follicle, oocyte and nucleus significantly increased as per advancement of age.